The Symbolic Meaning of the Baritan Tradition on the First Night of Syuro Rowosari Village, Kendal Regency - Febita Gita; Nur Fazlin; Marshanda Azmi Fawaz; Zahra Alfauziah; Khoirunnisa Khoirunnisa; Canakya Muhammad; Ahmad Salabi As-Silmi (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
Baritan is one of the traditions of an agricultural community that has been passed down from generation to generation in Rowosari Village, Kendal Regency. This tradition is carried out as a form of gratitude to God for the abundance of harvests and blessings received by the community. The commemoration of the night of One Syuro is an important moment in the implementation of Baritan, where people pray together and give offerings as a form of gratitude and hope that life will remain prosperous and avoid danger. Through this procession, Baritan not only functions as a religious ritual, but also strengthens social relations between residents. This ritual creates a close connection between the spiritual life, culture and social solidarity of the Rowosari Village community.